Cost-effectiveness analysis of colonoscopy and fecal immunochemical testing for colorectal cancer screening in China - Ren, Yinan; Zhao, Mingye; Zhou, Dachuang; Xing, Qian; Gong, Fangfang; Tang, Wenxi (Frontiers in Public Health, 2022)
Objective: This study aimed to evaluate the cost-effectiveness of the colorectal cancer screening in China, and that when the screening was implemented in a specific region. Methods: A 13-state Markov model was established to compare four screening protocols, including annual fecal immunochemical testing (FIT1), biennial fecal immunochemical testing (FIT2), electronic colonoscopy every 10 years (e-CSPY10), and electronic colonoscopy every 5 years (e-CSPY5), with no screening from the perspective of Chinese healthcare system. The model simulated the health states of a cohort of 100,000 average-risk individuals aging from 50 to 75. Additionally, scenarios including the implementation in a specific region, starting from 40, and incompletely successful treatment of cancer were also analyzed. Results: The results showed that both annual and biennial FIT for screening were dominant over no screening, and annual FIT was dominant over biennial FIT, saving 52.47CNY, 289.98CNY and 237.45CNY per person, and increasing 0.0705QALYs, 0.2341QALYs, and 0.1637QALYs, respectively. The ICER for e-CSPY relative to FIT were lower than the economic threshold, with that for e-CSPY10 were 7633.61CNY/QALY and 3461.47CNY/QALY compared with FIT1 and FIT2. The ICER for e-CSPY5 were 7470.16CNY/QALY and 4972.00CNY/QALY compared with FIT1 and FIT2. In addition, the ICER for e-CSPY5 relative to e-CSPY10 was 2313.65 CNY/QALY. Conclusion: It is worthwhile to popularize CRC screening in mainland China, as FIT always saving costs and colonoscopy is cost-effective. Regions with high income can take electronic colonoscopy every ten years, or even every five years into consideration when determining the specific strategies.